(3EbJUGO GdJfejI (B:s (3fXQjGJ(B- (3feGPL(B- (3GSJQGJjLjGJ (B/s - (3Hf bGfI, GSeGYjd eMeOs ((3YeGf(B: s (3OGQ CSGeI ddfTQ hGdJhRjY(B, s, 2011)
(3EbJUGO GdJfejI, GdeaGgje hHOGjGJ GdEgJeGe GdChdi(B- (3fXQjGJ GdJfejI hfeGPL Gdfeh(B- (3NjGQGJ GdJfejI hJMhd eaghegG aj GdacQ GdEbJUGOj GdeYGUQ(B- (3GdeTcdGJ hGdSjGSGJ GdJfehjI(B- (3Jehjd hJNWjW GdJfejI GdEbJUGOjIs
Keywords: (3GdEbJUGO GdJfejIs; (3GdJfejI GdELJeGYjIs; (3GdJfejI GdEbJUGOjIs